Potential therapeutic properties of Sorbus commixta twig ethanol extract on vitiligo in skin cells - Jung, Da Won; Lim, Su Jin; Lee, Chang Seok (Archives of Biological Sciences, 2021)
Paper description: Pre-We started this study to demonstrate the therapeutic properties of Sorbus commixta twig ethanol extract (STE) on vitiligo. Cell viability and melanin contents in STE-treated melanocytes were examined. Interleukin (IL)-6, -8 and tumor necrosis factor (TNF)-a expression were observed in dermal fibroblasts and keratinocytes by real-time PCR and ELISA. STE induced cell proliferation and melanin synthesis in melanocytes. STE inhibited IL-6, IL-8 and TNF-a expression in TNF-a-stimulated fibroblasts and keratinocytes. STE ameliorates vitiligo symptoms through melanin synthesis, antiinflammatory and antioxidative effects. Abstract: Sorbus commixta is a tree of the Rosaceae family growing in Asia that has long been used to treat asthma and neuralgia. In a previous report, the chemical isolated from the bark of S. commixta was shown to suppress the production of nitric oxide (NO) and preinflammation by downregulating the NF-кB pathway in lipopolysaccharide (LPS)-induced RAW 264.7 cells. Vitiligo is an acquired immune disease, usually characterized by white spots on the skin; however, its exact cause has not been identified. This study assessed the effects of an ethanol extract of S. commixta twigs (STE) on melanocyte activation, as well as its antiinflammatory and antioxidant properties. STE significantly increased the proliferation and melanin content of B16 melanocytes. Because of the importance of tumor necrosis factor (TNF)-α in inflammatory diseases, including the stimulation of vitiligo, the antiinflammatory effects of STE were tested in TNF-α-stimulated dermal fibroblasts and keratinocytes. STE reduced the levels of expression of IL-6, IL-8 and TNF-α mRNA and proteins. To assess the underlying molecular mechanism, the effects of STE on the mitogen-activated protein kinase (MAPK) signaling process were analyzed in dermal fibroblasts. Results show that STE inactivated extracellular signal-regulated kinase (ERK). In addition, STE exhibited antioxidative properties in assays of DPPH radical scavenging activity. Taken together, these findings suggest that STE has potential therapeutic activity in vitiligo.